CD4+, CD8+ and FOXP3+ lymphocytes infiltrating oral leukoplakia: an immunohistochemical analysis - Castro, Tamara Fernandes de [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Objective: To evaluate the infiltration of CD4+, CD8+ and FOXP3+ lymphocytes and their correlation with sociodemographic, clinicopathological and lifestyle characteristics of patients with oral leukoplakia. Patients and methods: Eighty patients diagnosed with oral leukoplakia were included in the study. Retrospective analyses were performed in order to verify the sociodemographic, clinicopathologic and lifestyle characteristics. The lymphocytic infiltrate characterization was performed by immunohistochemistry with antibodies against CD4+, CD8+, and FOXP3+ markers. Results: Of 80 patients included in the study, 60% were men, and their age ranged from 25 to 82 years, with a mean of 58.6. Thirty-eight patients (47.5%) were elderly, Thirty-two (40%) middle-aged, and only ten (10%) young adults. Sixty-one of the patients were smokers (76.2%) and forty-six were alcoholics (57.5%). Twenty-seven (35.5%) of the lesions presented some degree of dysplasia. The degree of epithelial dysplasia was correlated with the intensity of alcohol consumption (p=0.008). A positive correlation was found between CD4+ and CD8+ lymphocytes (p=0.005). Conclusion: The lymphocytic infiltrate of oral leukoplakia was not correlated with any clinicopathologic characteristic. However, the degree of epithelial dysplasia was correlated with the lifestyle of the patients.

Objetivo: Avaliar a infiltraçãdo dos linfócitos CD4+, CD8+ e FOXP3+ e sua correlação com caracteristicas sociodemográfica, clinicopatologicas e estilo de vida de pacientes com leucoplasias bucais. Pacientes e métodos: Oitenta pacientes com diagnóstico de leucoplasia bucal foram incluidos no estudo. Análises retrospectivas foram realizadas para verificar as características sociodemográficos, clinicopatológicos e estilo de vida dos pacientes. O infiltrado linfocitário foi caracterizado por imunoistoquímica com antígenos contra de CD4+, CD8+ e FOXP3+. Resultados: Dos 80 pacientes incluidos neste estudo, (60%) eram homens e a idade variou de 25 a 82 anos com idade média de 58,6 anos.Trinta e oito (47.5%) eram idosos, Trinta e dois (40%) eram adultos de meia idade e apenas dez (10%) adultos jovens. Sessenta e um dos pacientes eram fumantes (76.2%) e quarenta e seis eram etilistas (57.5%). Vinte e sete (35.5%) das lesões apresentaram algum grau de displasia epitelial. O grau de displasia epitelial apresentou correlação positiva com a intensidade do consumo do alcool (p=0.008). Houve correlação positiva entre os linfócitos CD4+ e CD8+ (p=0.005). Conclusão: O infiltrado linfocitário não foi relacionado com nenhuma característica clinicopatológica das lecoplasias bucais. Entretanto, o grau de displasia está relacionado ao estilo de vida dos pacientes.
Linfócitos CD4+, CD8+ e FOXP3+ que se infiltram na leucoplasia oral: uma análise imunohistoquimica.
Keywords: Leukoplakia; T-Lymphocytes; Immunohistochemistry; Leucoplasia; Linfócitos; Imuno-histoquímica